Effect of dietary n-3 series fatty acids on sperm production in the freshwater crayfish, Astacus leptodactylus (Eschscholtz) (Astacidae) - Harlioglu, Muzaffer Mustafa; Koprucu, Kenan; Harlioglu, Ayse Gul; Yonar, Serpil Mise; Duran, Tuba Cakmak; Cakmak, Mehmet Nuri; Gundogdu, Hande (Springer, 2013)
The objective of the present work was to evaluate the effects of three different rates of long chain n-3 polyunsaturated fatty acid (LC n-3 PUFA) on the sperm number of Astacus leptodactylus. The experiment was carried out with the four following treatments: control group (not supplemented LC n-3 PUFA), D1 (1 %), D2 (2 %) and D3 (3 %). The sperm number of A. leptodactylus was counted; the reproductive system was weighted; and the macroscopical analysis of the testes and vasa deferentia (DVD) were conducted. In addition, gonado-somatic index (GI) and testes index (TI) were also calculated. The results showed that there was a significant difference between the crayfish fed LC n-3 PUFA supplemented diets (D1, D2, D3) and control in mean sperm number (P < 0.05). The highest sperm number was found for the crayfish fed D3 (6.27 +/- A 0.14 x 10(8) sperm/distal vas deferens section). The results also showed that the reproductive system of the crayfish fed D3 and D2 was significantly heavier than that of the crayfish fed the control and D1 (P < 0.05). On the other hand, there was not a significant difference in the testes weight and vasa deferentia weight between the crayfish fed the control and D1, and between the crayfish fed D2 and D3 (P < 0.05). GI of the crayfish fed D3 and D2 was significantly higher than that of the crayfish fed control and D1 (P > 0.05), but there was not a significant difference in the TI of the crayfish fed control, D1, D2 and D3 (P > 0.05). In conclusion, diets containing different levels of LC n-3 PUFA significantly increase the sperm number of A. leptodactylus, and they are crucial for the production of higher number of sperm in this species.
Keywords: Astacus leptodactylus; Crayfish; Sperm number; n-3 Series fatty acid